Metode Pembiasaan Mendidik Anak dalam Perspektif Al-Ghazali dan Relevansinya di Era Modern - Mardliyah Mardliyah (Sekolah Tinggi Agama Islam Pati, 2022)
Child education is a crucial aspect for the development of children in the future. Therefore, parents have the obligation to educate, teach and train their children to become happy individuals in this world and the hereafter. This shows that education has significant importance. One of the methods that can be used in educating children is the method of habituation according to Al-Ghazali. This method of habituation has high relevance with child education in the modern era. This study aims to explore Al-Ghazali's ideas about the urgency of the habituation method in educating children and its relevance in the modern era. This research is a literature review since the data were obtained from various literature sources that have relevance to the research. The method and approach used in this research are qualitative descriptive. The analysis used content analysis by analyzing the relevant text content with the research. The primary data sources are the books